Multiresponsive hydrogels and organogels based on photocaged cysteine. Issue 48 (19th May 2021) - Rickhoff, Jonas; Cornelissen, Nicolas V.; Beuse, Thomas; Rentmeister, Andrea; Jan Ravoo, Bart
Abstract : Photocaged cysteine is a potent gelator for water as well as organic solvents and UV irradiation of these gels leads to controlled release of cysteine. Abstract : Here we present the readily accessible amino acid 4, 5-dimethoxy-2-nitrobenzyl-l -cysteine (DNC), as an ultra-low molecular weight gelator (MW = 316 g mol −1 ). Sonication of DNC in water or organic solvents as well as pH adjustment in water trigger gelation. A diverse set of stimuli (UV irradiation, oxidation, heat or pH change) induce a gel–sol transition. Moreover, the photo-triggered gel–sol transition was used to obtain a controlled cysteine release from the hydrogel.